Stability of atomic condensed systems with attractive two-body interactions - Tomio, L. [UNESP]; Filho, V. S. [UNESP]; Gammal, A.; Frederico, T. (My University, 2003)
In the present report, we review recent investigations that we have conducted on the stability of atomic condensed systems, when the two-body interaction is attractive. In particular, the dynamics that occurs in the condensate due to nonconservative terms is considered in the context of an extension of the mean-field Gross-Pitaevskii approximation. Considering the relative intensity of the nonconservative parameters, chaotic and solitonic solutions are verified. Also discussed is the possibility of a liquid-gas phase transition in the presence of positive three-body elastic collisions.